Emerging mycotoxins and reproductive effects in animals: A short review. Issue 12 (12th March 2022) - Chiminelli, Ilaria; Spicer, Leon J.; Maylem, Excel R. S.; Caloni, Francesca
Abstract: Emerging Fusarium mycotoxins beauvericin (BEA), enniatins (ENNs), and moniliformin (MON) are gaining increasing interest due to their wide presence especially in cereals and grain‐based products. In vitro and in vivo studies indicate that Fusarium mycotoxins can be implicated in reproductive disorders in animals. Of these mycotoxins, BEA may affect reproductive functions, impairing the development of oocytes in pigs and sheep. Studies show dramatic inhibitory effects of BEA and ENNA on bovine granulosa cell steroidogenesis. ENNs also inhibit boar sperm motility and cause detrimental effects on embryos in mice and pigs. Although little data are reported on reproductive effects of MON, in vitro studies show inhibitory effects of MON on Chinese hamster ovary cells. The present review aims to summarize the reproductive toxicological effects of emerging Fusarium mycotoxins BEA, ENNs, and MON on embryo development, ovarian function, and testicular function of animals. In vitro and in vivo toxicological data are reported although additional studies are needed for proper risk assessment. Abstract : Emerging Fusarium mycotoxins beauvericin (BEA), enniatins (ENNs) and moniliformin (MON) are gaining increasing interest due to their wide presence especially in cereals and grain‐based products. In vitro and in vivo studies indicate that Fusarium mycotoxins can be implicated in reproductive disorders in animals. The present review summarizes the reproductive toxicological effects of emerging Fusarium mycotoxins BEA, ENNs and MON on embryo development, ovarian function and testicular function of animals, but additional studies are needed for proper risk assessment.